"Based on actual facts": Documentary Inscription in Fiction Films. Issue 1 (2nd January 2021) - Carrera, Pilar
ABSTRACT: This article analyzes the discursive functions of the expression 'based on actual facts', or related utterances such as 'based on real events', 'based on a true story', 'inspired by a true story', etc., through which documentary rhetoric is inscribed in fiction films. It is concluded that one of these functions is to substract fictional stories from textual and ideological criticism by means of a supposed closeness to 'factuality', creating a simulacrum of discursive transparency. Through the formula 'based on real facts', and similar ones, reality is identified with a specific form of representation, i.e. with a particular rhetoric. This is produced through a double movement: on the one hand, it is assumed that documentary film is or should be a faithful reflection of a reality that precedes it, and that it is, as a discourse, subordinated to and at the service of that supposed pre-discursive reality; on the other hand, once this candid perspective on documentary narrative has been assumed, the fictional discourse that is said to be 'based on actual facts' endorses with the truth-effect of documentary narratives ('factual truth') the discourse on values that is characteristic of fiction.